Corrosion behavior of carburized 316 stainless steel in molten chloride salts. (15th July 2021) - Ren, Sen; Chen, Yanjun; Ye, Xiang-Xi; Jiang, Li; Yan, Shuai; Liang, Jianping; Yang, Xinmei; Leng, Bin; Li, Zhijun; Chen, Zezhong; Dai, Zhimin
Graphical abstract: Highlights: Vacuum carburisation of 316SS can greatly improve its hardness. Carburised 316SS shows much severer intergranular corrosion than 316SS. Corrosion is driven by redox reaction of metal impurities with Fe and Cr of 316SS. M7 C3 carbides at GBs are vulnerable to the attack by molten chloride salts. The decomposition of M7 C3 carbides reduce the hardness of carburised 316SS. Abstract: The corrosion has been investigated for carburized 316 stainless steel (SS) and 316SS in ternary molten NaCl-KCl-MgCl2 salt at 700 °C under argon atmosphere when adding Mg metal (1 wt%). Carburized 316SS has more severe intergranular corrosion than 316SS. Residual water and oxygen in the salts greatly oxidize Fe, Cr and Ni at the alloy surface in the initial stage of the corrosion process. Later, Fe and Cr at the alloy surface dissolve into salts through the redox reaction with metallic ion impurities such as Ni 2+, Fe 2+ and Fe 3+ in the salts. Cr-rich carbides at grain boundaries in carburized 316SS are vulnerable to attack by molten chloride salts because Cr atoms in the carbides preferentially escape from the carbides and dissolve into salts, causing the decomposition of Cr-rich carbides and reducing the hardness of carburized 316SS.